Training is an investment with return in temporary workers - Sobral, Filipa; Chambel, Maria José (Conferência - Investigação e Intervenção em Recursos Humanos, 2014)
This study investigates the impact of training on the employee–organisation relationship among a sample of temporary workers from a call centre (N= 240). The data support the idea that social exchange theories are useful frameworks in explaining temporary workers’ affective commitment towards organisations. Organisational investment in training was positively related to the affective commitment of these temporary workers. However, the employees attributed greater importance to the fact that training increased their employability than to the number of training hours received. The relationship between this human resource management practice and affective commitment partly occurred through the perceived organisational support on the part of the employees. Such perception partially mediates the relationship between training as a promoter of employability and this positive attitude.